Control of the mechanical systems by means of sliding modes and the solution to the problem of constraint reactions - Kotowski, S. (Archives of Mechanics, 1998)
A new method of determination of the constraint reactions in mechanics is introduced in this paper; the methods of investigation of the sliding modes in systems of variable structure are used.